Magnolia [videorecording (DVD)] - Brion, Jon (New Line platinum series., 2000)
Magnolia is a mosaic of American Life woven through a series of comic and poignant vignettes. Nine people will weave and warp through each other's lives on a day that builds to an unforgettable climax.